(untitled) (Journal of Cancer Research Updates, 2016)
Mammalian P-glycoproteins (P-gp) are members of the broad family of ABC transporters and play important physiological roles in establishing physical barriers that limit access of toxic compounds and thus in the pharmacokinetics of these compounds. Cancer cells exploit the presence of P-gp to fend off anti-cancer drugs, rendering them multidrug resistant (MDR). Structural investigations of P-gp involve the expression and isolation of this large integral membrane protein in high quality and in sufficient quantity for it to be amenable to electron microscopic (EM) and crystallographic studies. EM studies have defined the shape of the molecule and delineated its various conformations in solution but major breakthrough in obtaining atomic resolution structures of P-gp were accomplished by X-ray crystallography. Structures with increasing resolution and accuracy in various substrate and inhibitor bound forms are available for analysis and novel mechanistic insights have been obtained. These advances have paved the way for future research to further our understanding of the mechanism of P-gp function and development of potential inhibitors that may reverse MDR in cancer treatment.